2016
DOI: 10.4236/ojem.2016.43010
|View full text |Cite
|
Sign up to set email alerts
|

Air Plasma Spray for First Aid

Abstract: Hemorrhage during trauma occurred in emergency situations is a significant challenge. It may be life threatening if it is not treated swiftly. A new device which can effectively stop bleeding to save life of injured person, especially in battlefield situations and accidents, is presented. A plasma generator is designed to generate a low temperature air plasma spray for treating wounds. The spectral spike at 777.4 nm in the emission spectrum of the plasma plume and the spatial distribution of this emission line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Further tests on wounds of artery cuts at different locations will be useful to establish the treatment procedure in the first aid in any situation. A CAAP device, which can be made portable by using battery as the power source [51], should meet the requirements of advanced first aid [52].…”
Section: Discussionmentioning
confidence: 99%
“…Further tests on wounds of artery cuts at different locations will be useful to establish the treatment procedure in the first aid in any situation. A CAAP device, which can be made portable by using battery as the power source [51], should meet the requirements of advanced first aid [52].…”
Section: Discussionmentioning
confidence: 99%
“…Further tests on wounds of artery cuts at different locations will be useful to establish the treatment procedure in the first aid in any situation. A CAAP device, which can be made portable by using battery as the power source [32], should meet the requirements of advanced first aid [33]. It is understandable that the required treatment time to stop bleeding varies with the wound.…”
Section: Discussionmentioning
confidence: 99%
“…An emerging application is to develop lightweight portable devices for first aid, since microfluidic plasma jets can disinfect wound surface and enhance blood clotting without tissue damage [55]. In the study of Kuo [56], a portable handheld device which generated air plasma spray was used to stop wound bleeding, where pigs were used as animal models. It is revealed that the atomic oxygen species in plasmas can accelerate the coagulation process and meanwhile function as dry disinfectant.…”
Section: Plasma Jets Beyond Microchannelsmentioning
confidence: 99%
“…Furthermore, the hydrophilicity as well as the electrochemical properties are improved, with a contact-angle change from ~90° to ~20°, and an significantly improvement (5-fold) in specific capacitance (from 8.82 mF•cm −2 to 46.64 mF•cm −2 ). Reprinted with permission from [56]. Copyright 2016 Scientific Research Publishing Inc.; (c) An integrated system of a microfluidic plasma jet with a 3-axis platform for the surface functionalization of a carbon electrode.…”
Section: Plasma Jets Beyond Microchannelsmentioning
confidence: 99%